Staghorn stone in megapolycalicosis in a child: Still the case for open surgery? Case report - Antonio Marte (PAGEPress Publications, 2022)
We here report a rare case of congenital megapolycalicosis in a 14-year-old girl complicated by a 24-mm staghorn stone and numerous calculi at the level of all caliceal groups that had become symptomatic in recent weeks with malaise, hematuria, and urinary tract infection. Among the various therapeutic options, we opted for open surgery. The staghorn stone was removed by pyelotomy, and washout of the caliceal cavities released numerous microcalculi of 1.5−9 mm in size that were then removed. To our knowledge, this is the first case of pediatric megacapolycalicosis complicated by staghorn stone, which presents complex problems for the diagnosis and therapy.